Identification of muscarinic receptor subtypes involved in catecholamine secretion in adrenal medullary chromaffin cells by genetic deletion - Harada, Keita (Br J Pharmacol, 2015)
BACKGROUND AND PURPOSE: Activation of muscarinic receptors results in catecholamine secretion in adrenal chromaffin cells in many mammals, and muscarinic receptors partly mediate synaptic transmission from the splanchnic nerve, at least in guinea pigs. To elucidate the physiological functions of muscarinic receptors in chromaffin cells, it is necessary to identify the muscarinic receptor subtypes involved in excitation. EXPERIMENTAL APPROACH: To identify muscarinic receptors, pharmacological tools and strains of mice where one or several muscarinic receptor subtypes were genetically deleted were used. Cellular responses to muscarinic stimulation in isolated chromaffin cells were studied with the patch clamp technique and amperometry. KEY RESULTS: Muscarinic M(1), M(4) and M(5) receptors were immunologically detected in mouse chromaffin cells, and these receptors disappeared after the appropriate gene deletion. Mouse cells secreted catecholamines in response to muscarinic agonists, angiotensin II and a decrease in external pH. Genetic deletion of M(1), but not M(3), M(4) or M(5), receptors in mice abolished secretion in response to muscarine, but not to other stimuli. The muscarine-induced secretion was suppressed by MT7, a snake peptide toxin specific for M(1) receptors. Similarly, muscarine failed to induce an inward current in the presence of MT7 in mouse and rat chromaffin cells. The binding affinity of VU0255035 for the inhibition of muscarine-induced currents agreed with that for the M(1) receptor. CONCLUSIONS AND IMPLICATIONS: Based upon the effects of genetic deletion of muscarinic receptors and MT7, it is concluded that the M(1) receptor alone is responsible for muscarine-induced catecholamine secretion.